Isolation and characterization of hepatitis C virus resistant to a novel phenanthridinone derivative. Issue 5 (December 2015) - Ito, Wataru; Toyama, Masaaki; Okamoto, Mika; Ikeda, Masanori; Watashi, Koichi; Wakita, Takaji; Hashimoto, Yuichi; Baba, Masanori
Background: The novel phenanthridinone derivative HA-719 has recently been identified as a highly potent and selective inhibitor of hepatitis C virus replication. To elucidate its mechanism of inhibition, we have isolated and analyzed a clone of hepatitis C virus replicon cells resistant to HA-719. Methods: To isolate HA-719-resistant replicon cells, Huh-7 cells containing subgenomic hepatitis C virus replicons (genotype 1b) with a luciferase reporter (LucNeo#2) were cultured in the presence of G418 and escalating concentrations of HA-719. After several passages, total RNA was extracted from the growing cells, and Huh-7 cells were transfected with the extracted RNA. Limiting dilution of the transfected cells was performed to obtain an HA-719-resistant clone. Results: The 50% effective concentration (EC50 ) of HA-719 for hepatitis C virus replication was 0.058 ± 0.012 µM in LucNeo#2 cells. The replicon cells capable of growing in the presence of G418 and 3 µM HA-719 were obtained after 18 passages (72 days). The HA-719-resistant clone LucNeo719R showed 98.3-fold resistant to the compound (EC50  = 5.66 ± 0.92 µM), but the clone had no cross-resistance to telaprevir (NS3 inhibitor), daclatasvir (NS5A inhibitor), and VX-222 (NS5B inhibitor). The sequence analysis for the wild-type and LucNeo719R identified 3, 2 and 7 mutations in NS3/4 A, NS4B, and NS5A, respectively, but no mutations in NS5B. Conclusion: None of the amino acid mutations in the resistant clone corresponds to those reported to confer drug-resistance to current anti-hepatitis C virus agents, suggesting that the target of HA-719 for hepatitis C virus inhibition differs from those of the existing agents.